Radiological features of the intracranial extra-skeletal mesenchymal chondrosarcoma - Anas Abdallah; İrfan Çınar (Romanian Neurosurgery, 2021)
Background: Mesenchymal chondrosarcomas are the most malignant form of chondrosarcomas. They have mostly affected bones. Rarely, these tumors can be intracranial extraskeletal (IEMC) that originates from the meninges or parenchyma.